Integrated vector management targeting Anopheles darlingi populations decreases malaria incidence in an unstable transmission area, in the rural Brazilian Amazon - Martins-Campos, Keillen M. (2012)
Background: Studies on vector behaviour should be conducted in order to evaluate the effectiveness of vector control measures on malaria protection in endemic areas of Latin America, where P. vivax predominates. This work aims to investigate the fauna of anopheline mosquitoes and verify the impact of integrated vector management in two colonization projects in the Careiro Municipality, Western Brazilian Amazon. Methods. Four mosquitoes captures were carried out from August 2008 to March 2010, with an interval of six months between each collection. Since September 2009 a large programme to reduce the burden of malaria has started in the two communities by distribution of insecticide-treated bed nets (ITN) and intensification of indoor residual spraying (IRS). Human biting rates (HBRs), entomological inoculation rates (EIRs), malaria incidence rate (MIR) and Plasmodium carriers prevalence were used as outcomes to estimate the impact of the control measures. Results: A total of 3,189 anophelines were collected, belonging to 13 species. Anopheles darlingi was the predominant species in the period (42.6%), followed by Anopheles albitarsis (38.4%). An. darlingi HBRs showed a notable decreasing trend from the start to the end of the study. Conversely, An. albitarsis increased its contribution to overall HBRs throughout the study. For An. darlingi there was a significant positive correlation between HBRs and MIR (p=0.002). Anopheles albitarsis HBRs showed a significant negative correlation with the corresponding MIR (p=0.045). EIR from total anophelines and from An. darlingi and An. albitarsis presented decreasing patterns in the successive collections. Four species of anophelines (An. darlingi, An. albitarsis, Anopheles braziliensis and Anopheles nuneztovari) were naturally infected with Plasmodium, albeit at very low infection rates. There were a decrease in the MIR for both vivax and falciparum malaria and in the prevalence of Plasmodium vivax and Plasmodium falciparum carriers during the period of study. Conclusions: There is strong evidence of association between the density of An. darlingi and the incidence of malaria in the studies sites, further highlighting the importance of this vector in malaria transmission in this region. An. darlingi susceptibility to control using ITN and IRS is likely to be high in the rural settlements studied. © 2012 Martins-Campos et al.